2020
DOI: 10.1111/jcmm.16117
|View full text |Cite
|
Sign up to set email alerts
|

Anti–coronavirus disease 2019 (COVID‐19) targets and mechanisms of puerarin

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 35 publications
(66 reference statements)
0
35
0
Order By: Relevance
“…For instance, a meta-analysis showed that EGFR is involved in pathological effects on the COVID-19 inflammatory process [ 39 ]. A drug discovery study demonstrated that the anti-COVID-19 action of puerarin was associated with the suppression of oxidative stress and inflammatory cascades through the induction of EGFR [ 40 ]. In addition to the pharmaceutical targets, the mechanisms underlying the effect of biochanin A were discovered using pathway analysis.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a meta-analysis showed that EGFR is involved in pathological effects on the COVID-19 inflammatory process [ 39 ]. A drug discovery study demonstrated that the anti-COVID-19 action of puerarin was associated with the suppression of oxidative stress and inflammatory cascades through the induction of EGFR [ 40 ]. In addition to the pharmaceutical targets, the mechanisms underlying the effect of biochanin A were discovered using pathway analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular docking methodology was effective strategy to identify the binding ability of PA with core targets in CG. More computational procedures could be referenced as previous description 20 …”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, liver cancer target genes were attained through retrieving in GeneCard, OMIM, Oncodb.hcc databases [ 18 ]. All overlapping genes of oxyresveratrol and liver cancer were identified and exhibited by using Venn diagram analysis [ 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%